Crystal Structure and Structural Transformation of [(CH3)3NH]2[CuZn(CN)5]. Issue 4 (23rd January 2019) - Miyahara, Kana; Yoshida, Jun; Yuge, Hidetaka; Nishikiori, Shin‐ichi
Abstract : A newly synthesized coordination polymer, [(CH3 )3 NH]2 [CuZn(CN)5 ], was investigated using 13 C and 63 Cu solid‐state NMR techniques and single‐crystal X‐ray diffractometry. It consists of a three‐dimensional (3D) net composed of tetrahedral Cu I and Zn II ions and CN – ligands bridging between the two metal ions. (CH3 )3 NH + ions are trapped in the inner space of the 3D net. Three coordination sites of each metal ion are used for the formation of the 3D net and the remaining site is occupied by a unidentate CN – ligand. The structure of the 3D net is chiral and categorized assrs in the notation of the Reticular Chemistry Structure Resource (RCSR). In water vapor or open air at room temperature under ambient pressure, a powder of [(CH3 )3 NH]2 [CuZn(CN)5 ] showed a structural transformation to [(CH3 )3 NH][CuZn(CN)4 ]· 1.5H2 O, which is a known compound with a diamond‐like 3D net of [CuZn(CN)4 ] – composed of tetrahedral Cu I and Zn II ions and bridging CN – ligands. 63 Cu solid‐state NMR spectroscopy revealed that the Cu‐CN‐Zn orientation of the bridging CN – ligands was conserved after the structural transformation. Abstract :